Ivorybill hunters : the search for proof in a flooded wilderness - Hill, Geoffrey E. (Geoffrey Edward) (Oxford : Oxford University Press, 2007)
The author tells the story of how he and two of his colleagues stumbled upon what may be a breeding population of Ivory-billed Woodpeckers in the swamps of northern Florida. He relates their laborious attempts to document irrefutable evidence for the existence of this shy, elusive bird following the failure of a much larger team to do so.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Ivory-billed woodpecker -- Research -- Choctawhatchee River Watershed (Ala. and Fla.)